Quantifying cerebral microbleeds using quantitative susceptibility mapping from magnetization‐prepared rapid gradient‐echo - Naji, Nashwan; Gee, Myrlene; Jickling, Glen C.; Emery, Derek J.; Saad, Feryal; McCreary, Cheryl R.; Smith, Eric E.; Camicioli, Richard; Wilman, Alan H. (NMR in biomedicine, 2024)
T1‐weighted magnetization‐prepared rapid gradient‐echo (MPRAGE) is commonly included in brain studies for structural imaging using magnitude images; however, its phase images can provide an opportunity to assess microbleed burden using quantitative susceptibility mapping (QSM). This potential application for MPRAGE‐based QSM was evaluated using in vivo and simulated measurements. Possible factors affecting image quality were also explored. Detection sensitivity was evaluated against standard multiecho gradient echo (MEGE) QSM using 3‐T in vivo data of 15 subjects with a combined total of 108 confirmed microbleeds. The two methods were compared based on the microbleed size and susceptibility measurements. In addition, simulations explored the detection sensitivity of MPRAGE‐QSM at different representative magnetic field strengths and echo times using microbleeds of different size, susceptibility, and location. Results showed that in vivo microbleeds appeared to be smaller (× 0.54) and of higher mean susceptibility (× 1.9) on MPRAGE‐QSM than on MEGE‐QSM, but total susceptibility estimates were in closer agreement (slope: 0.97, r2: 0.94), and detection sensitivity was comparable. In simulations, QSM at 1.5 T had a low contrast‐to‐noise ratio that obscured the detection of many microbleeds. Signal‐to‐noise ratio (SNR) levels at 3 T and above resulted in better contrast and increased detection. The detection rates for microbleeds of minimum one‐voxel diameter and 0.4‐ppm susceptibility were 0.55, 0.80, and 0.88 at SNR levels of 1.5, 3, and 7 T, respectively. Size and total susceptibility estimates were more consistent than mean susceptibility estimates, which showed size‐dependent underestimation. MPRAGE‐QSM provides an opportunity to detect and quantify the size and susceptibility of microbleeds of at least one‐voxel diameter at B0 of 3 T or higher with no additional time cost, when standard T2*‐weighted images are not available or have inadequate spatial resolution. The total susceptibility measure is more robust against sequence variations and might allow combining data from different protocols. Quantifying microbleeds' susceptibility and size using QSM derived from MPRAGE was evaluated using in vivo and simulated measurements, in comparison with standard multiecho QSM. Results showed that the detection sensitivity of MPRAGE‐QSM was comparable with standard QSM. MPRAGE‐QSM provides an opportunity to detect and quantify the size and susceptibility of microbleeds of at least one‐voxel diameter at B0 ≥ 3 T with no additional time cost, when standard T2*w images are not available or have inadequate spatial resolution.